2007
DOI: 10.1080/09397140.2007.10638221
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and status of the Caracal,Caracal caracal,(Carnivora: Felidae), in the Abbasabad Naein Reserve, Iran

Abstract: A Caracal survey was carried out between 2002 and 2006 in the Abbasabad Reserve, which covers more than 300,000 ha in eastern Esfahan province and which is one of the best habitats for this species in Iran. It was found to occur mainly in desert mountains and hilly terrain where rodents and hares are abundant. 80% of direct observations were made from solitary individuals and the remainder in groups of two. Although rodents, hares and ground birds form the main part of the Caracal diet in Abbasabad Reserve, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…However, these species frequently diverge their use of shared resources, to reduce the effects of competition (Cáceres & Machado, 2013), through morphological (Bell, 1970; Hutchinson, 1959) or behavioural adaptations (Palomares & Caro, 1999). Common behavioural adaptations include spatial segregation, such as red fox ( Vulpes vulpes ) avoidance of habitat used by lynx ( Lynx lynx ; Farhadinia, Akbari, Beheshti, & Sadeghi, 2007). In addition, larger carnivores such as lion ( Panthera leo ), wild dog ( Lycaon pictus ), and cheetah ( Acinonyx jubatus ) exhibit temporal segregation while foraging in Kruger (South Africa) and Serengeti National Parks (Tanzania), (Mills & Biggs, 1993; Swanson et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, these species frequently diverge their use of shared resources, to reduce the effects of competition (Cáceres & Machado, 2013), through morphological (Bell, 1970; Hutchinson, 1959) or behavioural adaptations (Palomares & Caro, 1999). Common behavioural adaptations include spatial segregation, such as red fox ( Vulpes vulpes ) avoidance of habitat used by lynx ( Lynx lynx ; Farhadinia, Akbari, Beheshti, & Sadeghi, 2007). In addition, larger carnivores such as lion ( Panthera leo ), wild dog ( Lycaon pictus ), and cheetah ( Acinonyx jubatus ) exhibit temporal segregation while foraging in Kruger (South Africa) and Serengeti National Parks (Tanzania), (Mills & Biggs, 1993; Swanson et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Parental investment in caracals plays a large role in greater reproductive behavior. The time a mother spends with her kits (and the combined lack of post partum estrus) restricts females to one litter per year (Farhadinia et al 2007;Karami et al 2008). Once the young are conceived, males play no role in their direct or indirect care; females invest a great deal of time and energy into their young and a tree cavity, cave, or abandoned burrow is often chosen for parturition and the first four weeks of postnatal development (O'Brien and Johnson, 2007).…”
Section: Parental Investmentmentioning
confidence: 99%
“…However, the cat is so secretive and difficult to observe that its activity at daytime might easily go unnoticed and study in South Africa showed that caracals are most active when air temperature drops below 20 °C (68 °F); activity typically ceases at higher temperatures (Skinner and Chimimba, 2006). The solitary cat, the caracal mainly occurs alone or in pairs; the only group seen is of mothers with their offspring (Farhadinia et al 2007). Females in oestrus will temporarily pair with males (Avenant and Nel, 1998).…”
Section: Behaviourmentioning
confidence: 99%
See 2 more Smart Citations